Association between lactate to albumin ratio and mortality among sepsis associated acute kidney injury patients - Yaotang Wang; Haixia Yu (BMC Infectious Diseases)
Abstract Background Sepsis-Associated Acute Kidney Injury (SA-AKI) has high fatality rates, but clear outcome markers are lacking. The objective of this research was to ascertain the link between lactate-to-albumin ratio (LAR) and mortality in cases of SA-AKI. Methods We performed a retrospective cohort analysis of 3589 critically ill patients with SA-AKI using the Intensive Care Medical Information Mart IV (MIMIC-IV) database. Patients were categorized into four groups based on the quartiles of LAR. The findings of this study provide baseline data and outcomes regarding in-hospital, 30-day, and 90-day mortality rates for SA-AKI patients in the intensive care unit. We utilized multivariate cox regression analysis to compute the adjusted hazard ratio (HR) and 95% confidence intervals (95% CI). Subgroup analysis and restricted cubic spline curves were employed to further investigate the relationship between LAR and mortality. Results This study involved 3589 participants with a mean age of 62.5 years. Patients in the LAR group with a Q4 (LAR ≥ 0.95) were associated with an increased risk of in-hospital mortality, 30-day mortality, and 90-day mortality (hazards ratio (HR): 2.11, 95% CI:1.7–2.62; HR: 1.9, 95% CI: 1.55–2.34; HR: 1.91, 95% CI: 1.58–2.31, respectively). Notably, within the subgroup of patients with AKI stages 2 and no CHF patients, the association between LAR and mortality was more pronounced. Conclusion The research underscores that elevated LAR are linked to heightened mortality risks. Notably, subgroup analyses have demonstrated that the correlation between LAR and mortality is particularly robust in certain patient cohorts, most notably those with stage 2 AKI and those without congestive heart failure (CHF). Clinical trial number Not applicable.